1995
DOI: 10.3109/00365529509093231
|View full text |Cite
|
Sign up to set email alerts
|

Procoagulant and Prothrombotic Responses of Human Endothelium to Indomethacin and Endotoxin in Vitro Relevance to Non-Steroidal Anti-Inflammatory Drug Enteropathy

Abstract: Indomethacin induces PCA in HUVEC and augments LPS-induced PCA, while it abolishes the antithrombotic prostanoid response in these cells. These observations may be relevant to the microvascular injury and thrombosis observed in NSAID enteropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The studies indicated very different binding characteristics when compared with other ligands that bind to PLA 2 enzymes at the substrate-binding site. It was also reported that indomethacin abolishes the antithrombotic effect of PLA 2 (Nygard et al, 1995). This indicated that indomethacin might be involved in blocking its anti-coagulant binding site.…”
mentioning
confidence: 93%
“…The studies indicated very different binding characteristics when compared with other ligands that bind to PLA 2 enzymes at the substrate-binding site. It was also reported that indomethacin abolishes the antithrombotic effect of PLA 2 (Nygard et al, 1995). This indicated that indomethacin might be involved in blocking its anti-coagulant binding site.…”
mentioning
confidence: 93%
“…The first mechanism calls into play a direct action of indomethacin on liver vascular endothelium. Nygård et al have demonstrated that the exposure of cultured human umbilical vein cells (HUVEC) to indomethacin, either alone or in the presence of lipopolysaccharide (LPS), led to an increase in procoagulant activity [15]. In particular, LPS application to endothelial cells resulted both in the induction of procoagulant activity and the release of 6-keto-prostaglandin F 1α (the stable metabolite of prostacyclin) and prostaglandin E 2 , as protective responses deputed to maintain the patency of vascular blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, LPS application to endothelial cells resulted both in the induction of procoagulant activity and the release of 6-keto-prostaglandin F 1α (the stable metabolite of prostacyclin) and prostaglandin E 2 , as protective responses deputed to maintain the patency of vascular blood flow. When HUVEC were cultured in the presence of indomethacin and LPS, the prostanoid production was suppressed, and the procoagulant response increased up to the induction of pro-thrombotic alterations [15]. In keeping with these findings, a study on rats with portal hypertension showed that the concomitant administration of indomethacin and low-dose aspirin resulted in a loss of antithrombotic protection by aspirin on portal endothelium [16].…”
Section: Discussionmentioning
confidence: 99%
“…For example, compound 14 for which the strong binding affinity (09.1 pki), lower binding energy ()22.5), and high GOLD fitness score (67.76) were observed showed the binding interaction similar to that of indomethacin (Table 1). From the docked conformation, it was also predicted that the oxygen atom of hydroxyl group attached to the pyrrolidine ring and nitrogen atom in pyridine ring of the compound 14 established interaction with the amino acid residues Asp 49 , Gly 30 , His 40 , and Lys 69 in a similar manner of indomethacin to the same residues ( Figure 3A,B). Similarly, it was also predicted that the oxygen atoms attached to the sulfur atom in compound 27 interact in the same fashion to the important residues of the enzyme ( Figure 3C).…”
Section: Binding Interactions Of Finally Selected Compoundsmentioning
confidence: 98%
“…These studies demonstrate that the binding mode of indomethacin is very different as compare to other molecules that bind to the substrate binding site of PLA 2 enzyme. It was also indicated that indomethacin blocks the anti‐thrombotic action of PLA 2 , thus suggesting that indomethacin might also be involved in inhibiting its anti‐coagulant binding site (40). Very recently, the co‐crystallized structure of PLA 2 with indomethacin has been resolved, to understand its binding mode with PLA 2 and the mechanisms of its actions against both catalytic and anti‐coagulant actions.…”
mentioning
confidence: 99%